Linear convergence rates for extrapolated fixed point algorithms. (2nd January 2019) - Bargetz, Christian; Kolobov, Victor I.; Reich, Simeon; Zalas, Rafał
ABSTRACT: We establish linear convergence rates for a certain class of extrapolated fixed point algorithms which are based on dynamic string-averaging methods in a real Hilbert space. This applies, in particular, to the extrapolated simultaneous and cyclic cutter methods. Our analysis covers the cases of both metric and subgradient projections.